Systemic inflammatory responses to repeated and increasing endotoxin challenges in fetal sheep - Sanya Kathuria; Akash Gupta; Ayna R. Tracy; Rosa I. Luna Ramirez; Senthil Kumar Thulasingam; Nahla Zaghloul; Mohamed Ahmed; Sean W. Limesand (Physiological Reports)
Abstract Repeated low‐dose administration of lipopolysaccharide (LPS) attenuates subsequent fetal responses, which makes it challenging to investigate interventions to prolonged exposure. Our aim was to develop a fetal inflammatory response syndrome (FIRS) model that consistently and effectively elicits a marked physiological response to increasing LPS doses. Four intravenous LPS boluses (0.3, 1.5, 3, and 15 μg) were administered to fetal sheep over 5 days. Physiological responses were measured via blood gases, pH, lactate, and cortisol concentrations. Fetal peripheral blood mononuclear cells (PBMCs) were analyzed for transcriptomic changes and tissue cytokine expression postmortem. All LPS challenges increased lactate, cortisol, and pCO2 concentrations and decreased pH and pO2 levels at 3 and 5 hours. No interaction was found between day (increasing LPS doses) and hour (LPS response to each dose). PBMC numbers increase with LPS challenges. Transcriptional analysis on PBMCs identified several enriched gene clusters indicating upregulation of inflammatory gene signatures along with complement activation and NFκB signaling pathways. Expression of pro‐inflammatory cytokines (TNFα, IL‐6, or IL‐1β) was measured in lung, heart, liver, placenta, and spleen. Physiological indices show both respiratory and metabolic acidosis with successive and increasing LPS challenges that demonstrate a robust systemic response despite tachyphylaxis to LPS in fetal sheep.